Development of a Drosophila melanogaster spliceosensor system for in vivo high-throughput screening in myotonic dystrophy type 1 - Irma García-Alcover; Jordi Colonques-Bellmunt; Raquel Garijo; José R. Tormo; Rubén Artero; Mari Carmen Álvarez-Abril; Arturo López Castel; Manuel Pérez-Alonso (The Company of Biologists, 2014)
Alternative splicing of pre-mRNAs is an important mechanism that regulates cellular function in higher eukaryotes. A growing number of human genetic diseases involve splicing defects that are directly connected to their pathology. In myotonic dystrophy type 1 (DM1), several clinical manifestations have been proposed to be the consequence of tissue-specific missplicing of numerous genes. These events are triggered by an RNA gain-of-function and resultant deregulation of specific RNA-binding factors, such as the nuclear sequestration of muscleblind-like family factors (MBNL1-MBNL3). Thus, the identification of chemical modulators of splicing events could lead to the development of the first valid therapy for DM1 patients. To this end, we have generated and validated transgenic flies that contain a luciferase-reporter-based system that is coupled to the expression of MBNL1-reliant splicing (spliceosensor flies), to assess events that are deregulated in DM1 patients in a relevant disease tissue. We then developed an innovative 96-well plate screening platform to carry out in vivo high-throughput pharmacological screening (HTS) with the spliceosensor model. After a large-scale evaluation (>16,000 chemical entities), several reliable splicing modulators (hits) were identified. Hit validation steps recognized separate DM1-linked therapeutic traits for some of the hits, which corroborated the feasibility of the approach described herein to reveal promising drug candidates to correct missplicing in DM1. This powerful Drosophila-based screening tool might also be applied in other disease models displaying abnormal alternative splicing, thus offering myriad uses in drug discovery.